2022
DOI: 10.1007/s43630-022-00287-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast transient absorption and solvation of a super-photoacid in acetoneous environments

Abstract: The phenomenon of photoacidity, i.e., an increase in acidity by several orders of magnitude upon electronic excitation, is frequently encountered in aromatic alcohols capable of transferring a proton to a suitable acceptor. A promising new class of neutral super-photoacids based on pyranine derivatives has been shown to exhibit pronounced solvatochromic effects. To disclose the underlying mechanisms contributing to excited-state proton transfer (ESPT) and the temporal characteristics of solvation and ESPT, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…[61][62] In other words, any MCH can be used to perturb acid-base equilibria featuring an equilibrium constant that is higher than that of its ground state, but lower than that of its metastable state. [63] A recent work by Wachtveitl and co-workers, [25] however, suggests that the phenolic site of MCHs can be regarded to as a "superphotoacid" [64] and deprotonation precedes any other thermal decay (see below for a more detailed discussion). Hence, the unrivalled capability of MCHs to display persistent proton dissociation in water results from the possibility to photochemically populate a conjugate base that is metastable.…”
Section: In Quest Of Persistent and Reversible Photoacidsmentioning
confidence: 99%
“…[61][62] In other words, any MCH can be used to perturb acid-base equilibria featuring an equilibrium constant that is higher than that of its ground state, but lower than that of its metastable state. [63] A recent work by Wachtveitl and co-workers, [25] however, suggests that the phenolic site of MCHs can be regarded to as a "superphotoacid" [64] and deprotonation precedes any other thermal decay (see below for a more detailed discussion). Hence, the unrivalled capability of MCHs to display persistent proton dissociation in water results from the possibility to photochemically populate a conjugate base that is metastable.…”
Section: In Quest Of Persistent and Reversible Photoacidsmentioning
confidence: 99%
“…Similarly, the study in neat acetone did not fully answer the question regarding the actual proton acceptor, keeping the possibility of ESPT to acetone still unsettled. 61 In a previous computational study, we have applied the Fo ¨rster cycle (Fig. 2) to determine the pK Ã a values of the photoacids A-F in the related solvent DMSO through the ground-state pK a and electronic transition energies.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, the ESPT of photoacid B has been studied experimentally in acetone–water mixtures 60 and neat acetone. 61 The study in acetone–water mixtures showed that a reaction complex between the photoacid and water—formed either already in the ground state or directly after excitation—becomes crucial for the ESPT dynamics of photoacid B in these solvent mixtures. 60 In particular, association constants could be determined from the changes in the UV/Vis absorption spectra, but more detailed spectroscopic information on such intermediates was not directly accessible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solvatochromic properties as well as ESPT kinetics , have been studied experimentally in a variety of solvents including water, methanol, ethanol, and DMSO. Recently, the dynamics and ESPT intermediates of a strongly hydrogen-bonded complex of compound A with a trialkylphosphine oxide in nitrile solution were elucidated. , Furthermore, for the strongest superphotoacid B of that class, namely tris­(1,1,1,3,3,3-hexafluoropropan-2-yl)-8-hydroxypyrene-1,3,6-trisulfonate (p K a * ≈ −4 in water), the possibility of ESPT in acetone–water mixtures and in neat acetone were demonstrated . Despite the wealth of experimental knowledge regarding this photoacid, only limited information on the molecular origin of the exceptionally high photoacidity is yet available in the literature.…”
Section: Introductionmentioning
confidence: 99%